EVALUATING THE IMPACT OF AI-ENABLED CLOUD COMMUNICATION PLATFORMS ON STUDENT ENGAGEMENT IN HIGHER EDUCATION: A CASE OF AFGHANISTAN PRIVATE UNIVERSITIES - Sadat, Mir Mohammad Naim; Tokhi, Mustafa; Azizi, Muhammad Ajmal; Esmati, Shahabuddin; Emynorane, Ralaivao Hanginiaina (Global Education Trends, 2025)
The integration of artificial intelligence (AI) and cloud-based technologies is reshaping higher education globally, yet their impact in fragile contexts remains underexplored. This study evaluates the influence of AI-enabled cloud communication platforms on student engagement in ten private universities in Afghanistan, with a focus on interaction, personalization, motivation, and collaboration. A qualitative research design was employed, using classroom and online observations, document analysis, and semi-structured interviews with faculty, students, and administrators. The findings reveal that these platforms significantly enhanced engagement by fostering real-time communication, adaptive feedback, gamification, and collaborative learning opportunities. However, effectiveness was constrained by infrastructure weaknesses, uneven institutional readiness, limited faculty training, and cultural skepticism regarding AI. The study highlights that technology alone cannot transform education without supportive ecosystems of infrastructure, pedagogy, and ethical guidelines. Its impact lies in providing evidence for policymakers, educators, and administrators seeking to strengthen student-centered learning and digital transformation in higher education. The study suggests future research should adopt mixed methods approaches to measure learning outcomes more systematically, expand to public universities, and explore long-term cultural and ethical implications of AI integration, ensuring digital innovation contributes to equitable and sustainable educational reform in Afghanistan and comparable contexts.